PROMOSI BUDAYA DAN PARIWISATA BERBASIS MEDIA DIGITAL: MENINGKATKAN KESADARAN KAUM MUDA TERHADAP WARISAN BUDAYA LOKAL - Yustus Sentus Halum; Ely Heldydiana Selamat; Theodisius Frederico Rondas; Yohanes Christian Mbohong; Yohanes Day Nagi (Randang Tana - Jurnal Pengabdian Masyarakat, 2021)
As an effort to preserve cultural heritage which can also be an attraction in the tourism sector, social media is a digital media that is familiar to use among young people. The internet can have potential as a medium for community empowerment itself. Based on the thoughts, the implementing team for this Community Service activity has carried out community service activities with the title "Digital Media-Based Culture and Tourism Promotion: Raising Youth Awareness of Local Cultural Heritage." The scope of the implementation of this service activity is in the fields of culture and tourism education which is adjusted to the minor profile of the implementing team's study program. The places where PkM activities are carried out are Langgo Village and Ruteng Pu'u Village with different activity times. In general, this Community Service activity was carried out well. This can be seen in the achievements of the activities carried out in accordance with the situation analysis and the initial plan of activities. Nevertheless, the implementing team acknowledged that there were several planned activities that could not be implemented due to the pandemic situation and restrictions on public activities that were currently taking place. Finally, the implementation of service activities has implications for the unavoidable trend of going digital. This trend can be one of the breakthroughs that change the way tourism and local culture are promoted more broadly, effectively, and modernly. With digital-based promotions, the reach of tourist information and various cultural arts performances will touch all levels of society in various regions with a wide reach, anytime and anywhere